The politics of accountability in Southeast Asia the dominance of moral ideologies - Rodan, Garry 1955-; Hughes, Caroline 1969- (Oxford Oxford University Press, 2014)
This volume examines different ideologies and related political coalitions forming the bases of movements for accountability reform in Southeast Asia.
Includes bibliographical references and index.
Keywords: Government accountability -- Southeast Asia; Democracy -- Southeast Asia; Southeast Asia -- Politics and government